Analisis Kewenangan Jaksa dalam Tindak Pidana di Bidang Pertanahan - Primadwiyani, Anak Agung Anisca; Yusa, I Gede; Primantari, Anak Agung Angga (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024)DO - 10.24843/AC.2024.v09.i02.p07, 2024)
The purpose of writing this article is to conduct an in-depth analysis of the criminal provisions of the land area as well as to analyze the authority of the prosecution in the handling of cases of land crime. As for the method of research used, it is the normative legal method. The results of the research show that the criminal procedure in the field of land, listed in Article 167 of the Covenant, relates to crimes against land abduction; Articles 263, 264, and 274 of the Code relate to the crime against counterfeiting of letters; and Article 385 of the Convention relates to the crime of obscuring the right to immovable goods such as land and houses, commonly referred to as stellionate crimes. The authority of the prosecutor in criminal matters is to prosecute, execute judges' ordinances and court decisions that have acquired fixed legal force, supervise the execution of conditional criminal judgments, supervisory criminal decisions, and conditional rulings, conduct investigations of certain criminal acts under the law, supplement the file of certain cases, and for that purpose, carry out additional inspections before being referred to the court in its execution coordinated with the investigator. For alleged criminal acts in the field of agriculture that meet the elements contained in Articles 167, 242, 263, 264, 274, and 385 of the Covenant,.